(untitled) (Colombia Medica, 1986)
Between 1978 and 1983, 35 neonates with coarctation of the aorta (from a group of 200 cases with the same pathology) underwent coarctation relief (all cases are from the Cardiovascular Pediatric Service of National Remission Hospital). Indications for the operation were persistent heart failure and/or hypertension. Three surgical techniques were employed: autoplasty with the prosthetic patch (politetrafluoroenthlyen) in 23 cases. Repair with subclavian flap in 11 cases and resection of coarctate segment with end-to-end anastomosis in only one case. It is an important fact the high incidence of congenital cardiac malformations is associated with coarctation of the aorta in neonates. There were 8 deaths (six of them with associated cardiac malformations and another with miocardiopathy). There were 5 cases with restenosis and no hypertension cases. All others are good in the follow-up. Any of them are waiting for the definitive correction of their major cardiac malformation. The high risk of mortality in this group marks again the importance of adequate medical treatment before surgical correction in optimal conditions and as soon as possible.